Nuts, anchor, self-locking, floating, two lug, incremental counterbore, in alloy steel, cadmium plated MoS2 lubricated. Classification: 900 MPa (at ambient temperature) /235°C. (15th December 1996) - British Standards Institution,
No abstract available